Stabilization of human RNA and DNA in stool samples at room temperature - Preywisch, Regina (BioTechniques, 2025)
This study examines the stability of human mRNA and DNA in stool samples for noninvasive gastrointestinal disease detection. While stool samples are valuable for diagnosing conditions like inflammatory disorders and colorectal cancer, mRNA instability poses significant challenges, risking false-negative results. To investigate this, 97 stool samples were treated with a specialized stabilizing solution and stored at room temperature, with analyses conducted on Day 1 and Day 15. The research aimed to improve storage protocols for enhanced reliability in mRNA diagnostics, aiding in personalized medicine and biomarker discovery. Results showed variability in total nucleic acid yields, increasing from Day 1 (mean 112 ng/µL) to Day 15 (mean 165 ng/µL), highlighting the benefits of improved homogenization and bacterial lysis. Human DNA remained stable over the 14-day period. For RNA stability, three mRNA markers were analyzed: Carcinoembryonic Antigen (CEACAM5), Prostaglandin-Endoperoxide Synthase 2 (PTGS2) and cortactin (CTTN). Both CEACAM5 (p=0.064) and PTGS2 (p=0.79) maintained stability, while CTTN showed a statistically significant but only modest reduction in expression (p < 0.0001). Overall, the stabilization buffer proved effectiveness in preserving nucleic acids and provided insights into mRNA marker stability over time